Aortic valve replacement among patients with Alzheimer's disease and related dementias. Issue 12 (8th September 2021) - Hollenbeck, Brent K.; Dunn, Rodney L.; Sukul, Devraj; Modi, Parth K.; Nallamothu, Brahmajee K.; Sen, Ananda; Bynum, Julie P.
Abstract: Background: Transcatheter aortic valve replacement (TAVR) has made palliation from aortic stenosis more broadly available to populations previously thought to be too high risk for surgery, such as those with Alzheimer's disease and related dementias (ADRD); however, its safety and effectiveness in this context are uncertain. Methods: We performed a retrospective cohort study of national Medicare beneficiaries, aged 66 and older with Parts A and B, between 2010 and 2016. Patients undergoing AVR were identified, and follow‐up was available through 2017. Multivariable regression was used to measure the independent association between having a diagnosis of ADRD at the time of AVR, stratified by TAVR and surgery, and outcomes (mortality and Medicare institutional days at 1 year after AVR). Results: The average rate of increase in AVR per year was 17.5 cases per 100, 000 ADRD and 8.4 per 100, 000 non‐ADRD beneficiaries, largely driven by more rapid adoption of TAVR. Adjusted mortality following AVR declined significantly between those treated in 2010 and 2016, from 13.5% (95% CI 10.2%–17.7%) to 6.3% (95% CI 5.2%–7.6%) and from 13.7% (95% CI 12.7%–14.7%) to 6.3% (95% CI 5.8%–6.9%) in those with and without ADRD, respectively. The sharpest decline was noted for patients undergoing TAVR between 2011 and 2016, with adjusted mortality declining from 19.9% (95% CI 11.2%–32.8%) to 5.2% (95% CI 4.1%–6.5%) and from 12.2% (95% CI 9.3%–15.8%) to 5.0% (95% CI 4.4%–5.6%) in patients with and without ADRD, respectively. Similar declines were evident for Medicare institutional days in the year after AVR in both patient groups. Conclusions: Rates of AVR in those with ADRD increased during the past decade largely driven by the diffusion of TAVR. The use of TAVR in this vulnerable population did not come at the expense of increasing Medicare institutional days or mortality at 1‐year.